The Quranic Miracle of and its impact on rhetorical thought - Sadullah Salim, Abdullah; Ali Mahmood, Nashat (Zanco Journal of Human Sciences, 2023)
Abstract Praise is to God, Lord of the Worlds, and may prayers and peace be upon the Messenger as a mercy to the worlds. Then: It is worth saying that the Arabic rhetoric is closely related to the miracleles in Holly Quran, due to the nature of the investigations that they dealt with and the topics they dealt with, because the systems of the Great Qur’an were among the most fluent and eloquent systems; Scholars and masters of rhetoric rushed to search for the requirements of this eloquent system, and to investigate its most important characteristics and manifestations that combine in crowning the systems and crowning it with highness and transcendence. So the means were mixed with the aims, and the issues of rhetorical research were combined with the issue of miraculousness, a combination that eluded separation and fragmentation, so research in the miraculous made speech necessary to extrapolate and employ rhetorical researchers, and vice versa. In addition, the one who examines the early beginnings of rhetoric will find that it met on one level with the beginnings of research in the miraculous by a group of distinguished scholars in the third century, such as Abu Ubaidah Muammar bin Al-Muthanna (209 AH), Al-Jahiz (255 AH), Al-Ramani (384 AH) and Al-Khattabi ( 388 AH) and Al-Baqlani (403 AH), their writings were rich sources on which scholars later relied on despite of their different backgrounds and different specializations. From this point, this research came under the title (The Miracle of the Qur’an and its Effect on Rhetorical Thought) and included a preface in which it dealt with the works of the miraculousness of the Qur’an and their impact on rhetorical thought. Rhetorical research in standing on the most important features of the miraculous and its secrets. Then the research culminated by mentioning a summary of the findings of the research. of view, research on miracles has gained great importance in linguistic studies. Especially rhetorical, because the topics he deals with are related to the systems of the Holly Qur’an; which represents the highest levels of eloquence and rhetoric.